FREEDOM OF EXPRESSION: THE TENSION BETWEEN THE PRESS, THE CITIZEN AND NATIONAL SECURITY - Victor AGANBI, (IJRDO - Journal of Social Science and Humanities Research, 2020)
— Journalists are accorded several privileges and rights under the laws of many countries, as well as under international law. The limits and boundaries to journalist privileges and rights are increasingly obfuscated and raises the question whether these freedoms are shielded from the operation of National Security? On the other hand, the impact of emergent digital technologies, the internet and social media which have empowered the average person to perform the functions of a journalist coupled with the resultant rise of fake news is potentially incredibly dangerous. The internet has challenged many of the definitions of a journalist and thus who should be protected. This study interrogates the concepts ofJournalists’ freedoms and national security in Nigeria and attempts to address the relationship between the claim to privileged communications by journalists and the government’s right to ensure safety of the citizens. This research adopts a non-doctrinal, multi-disciplinary methods.